Analisis Penerapan Model Pembelajaran Kontekstual Terhadap Kemampuan Berpikir Kreatif Mata Pelajaran Ekonomi Siswa Kelas XI IPS MA Manbaul Ulum Tahun Ajaran 2024 - 2025: Penelitian - Muhammad Raziqin; Miftahus Surur; Dassucik (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is motivated by issues observed in the teaching and learning process, where several problems still arise during classroom activities. The current learning model has not maximized its potential, resulting in a lack of enhancement in students' creative thinking skills. To address this, it is essential for educators to implement learning models that can effectively improve creative thinking abilities. The contextual learning model, which connects taught material with real-world contexts and students' environments, can encourage students to think creatively in class. This study employs a qualitative research method, conducted from July to August at MA Manbaul Ulum. Data collection techniques included observation, interviews, and documentation. The findings indicate that from the insights of twenty-one sources, comprising one economics teacher and twenty XI IPS students, the contextual learning model is highly effective in enhancing students' creative thinking skills in economics at MA Manbaul Ulum.